ON THE BOOTSTRAP METHOD OF ESTIMATION OF RESPONSE SURFACE FUNCTION - Szerszunowicz, Małgorzata (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
Nowadays, in many fields of science it is necessary to carry out miscellaneous analyses using classical statistical methods, which usually have correct assumptions. These assumptions in the research realities cannot always be met, which makes it impossible to carry out analyses and leads to incorrect conclusions and recommendations.The study of the production process largely consists in the use of tools of statistical quality control which are based on classical statistical methods. These methods result in some improvements in technological and economic results of the manufacturing process. One of the tools of statistical quality control is the design of experiments, whose important element is the estimation of response surface function.The aim of this paper is to present the bootstrap method of estimation of response surface function and its use for empirical data.